Translation is a mode=Translation is an anti-neocolonial mode - Choi, Don Mee (2020 Pamphlet Series., 2020)
"Don Mee Choi is the author of three books of poetry and hybrid essays, and an award-winning translator of contemporary Korean women's poetry. In this pamphlet, Translation is a Mode=Translation is an Anti-neocolonial Mode, she explores translation and language in the context of US imperialism--through the eyes of a "foreigner;" a translator; a child in Timoka, the made-up city of Ingmar Bergman's The Silence; a child from a neocolony."--Publisher's website (viewed 2021 February 10).